Flatness-based open-loop and closed-loop control for electrostatic quasi-static microscanners using jerk-limited trajectory design. (December 2018) - Schroedter, Richard; Roth, Matthias; Janschek, Klaus; Sandner, Thilo
Highlights: The open-loop and closed-loop control for a quasi-static micro scanner is shown. The nonlinear mechatronic system model is parameterized by measurements. Jerk-limited trajectories in physical limits allow avoiding residual oscillation. Based on flatness an extended PIDk controller and a Luenberger observer are used. The performance improvement is validated by experimental results. Graphical abstract: Abstract: This paper describes the open-loop and closed-loop control for quasi-static microscanners exploiting the inherent flatness property. The developed nonlinear control method is verified on a gimbaled quasi-static/resonant scanning micro mirror with electrostatic staggered vertical comb (SVC) drive actuation. Based on a mechatronic micro mirror model, we present a flatness-based feed forward control method using jerk-limited trajectories to reduce undesired oscillations. For the closed-loop control we introduce a stabilizing linearizing feedback including an extended Luenberger observer for improvement of the command tracking in presence of model inaccuracies. The experimental results for both scenarios, open-loop and closed-loop control, are compared with simulations and further assessed in terms of performance and feasibility for industrial application.